Tackling multidrug resistance mediated by efflux transporters in tumor-initiating cells. (2nd June 2016) - McIntosh, Kyle; Balch, Curt; Tiwari, Amit K.
ABSTRACT: Introduction : Expression of the multifunctional ATP-binding cassette (ABC) efflux transporter gene family is a well-established mechanism for protecting cancer stem cells (CSCs) from damage or death due to toxins. The outcome of such protection makes CSCs innately multidrug resistant (MDR) to conventional chemotherapy. Areas covered : While research has focused on gaining better insight into the role of ABC transporters in CSC drug resistance, various strategies to circumvent the function of these transporters have been proposed, including inhibition of transporter function through targeted tyrosine kinase inhibitors, competitive and allosteric modulators, shRNA-mediated inhibition, nanoparticle-mediated delivery of inhibitors, and modulating the regulation of transcriptional and signaling pathways involving ABC transporters. This review highlights the role of MDR mediated by ABC transporters, particularly in CSCs, and the current progress and pitfalls of strategies to circumvent MDR in CSCs. Expert opinion : Cancer stem cells are now a subject of intense research, as it is hypothesized that these progenitors predominantly beget tumorigenesis, chemoresistance, and metastasis. Consequently, the design and synthesis of more effective ABC transporter inhibitors, to increase cytotoxic drug concentrations in CSCs (thus increasing their eradication), is a promising approach for the field of oncology.